Effect of glycine addition on the in-vitro corrosion behavior of AZ31 magnesium alloy in Hank's solution. (10th August 2021) - Pokharel, Durga Bhakta; Wu, Liping; Dong, Junhua; Yadav, Amar Prasad; Subedi, Dhruba Babu; Dhakal, Madhusudan; Zha, Lin; Mu, Xin; Umoh, Aniefiok Joseph; Ke, Wei
Abstract: This study reports on the effect of the addition of Glycine to Hank's solution on the in-vitro corrosion behavior of AZ31 magnesium (Mg) alloy at 37 ℃ and a pH of 7.4 studied by using potentiodynamic polarization (PDP), hydrogen collecting techniques and electrochemical impedance spectroscopy (EIS) in combination with surface characterization techniques such as optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy analysis (XPS). The results reveal that adsorption of glycine initially subdues the dissolution of AZ31 Mg alloy while in long run it enhances the dissolution of the alloy due to the commencement of the chelation effect of glycine with Ca 2+ released from hydroxyapatite. The chelation of glycine with Ca 2+ induces the formation of cracks in the surface film which further promotes the dissolution of AZ31 Mg alloy thereby forming a porous corrosion products layer on the surface of the alloy. As a result, both the continuous dissolution of AZ31 magnesium alloy and the hydrogen evolution rate (HER) are enhanced with increasing the immersion time in Hank's solution.